2018
DOI: 10.1007/s13311-018-0628-1
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Plays a Role in Alzheimer's Disease by Negatively Regulating Aβ42

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia. Pigment epithelium-derived factor (PEDF), a unique neurotrophic protein, decreases with aging. Previous reports have conflicted regarding whether the PEDF concentration is altered in AD patients. In addition, the effect of PEDF on AD has not been documented. Here, we tested serum samples of 31 AD patients and 271 normal controls. We found that compared to PEDF levels in young and middle-aged control subjects, PEDF levels were reduced in old-aged co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…[63] PEDF has been shown to have neurotrophic and neuroprotective effects, and has been implicated in the pathogenesis of Alzheimer's Disease. [64] Additionally MMP-1, a protease which has been implicated in lung fibrosis, interstitial pneumonia, and cancer, was found to be important in our model. [65,66] Proteases have a prominent role in cancer, coronary disease, and OAD.…”
Section: Plos Computational Biologymentioning
confidence: 69%
“…[63] PEDF has been shown to have neurotrophic and neuroprotective effects, and has been implicated in the pathogenesis of Alzheimer's Disease. [64] Additionally MMP-1, a protease which has been implicated in lung fibrosis, interstitial pneumonia, and cancer, was found to be important in our model. [65,66] Proteases have a prominent role in cancer, coronary disease, and OAD.…”
Section: Plos Computational Biologymentioning
confidence: 69%
“…Therefore, PEDF affects various stem cell populations in the development of bone, brain, muscle, and eye (Sagheer, Gong, & Chung, 2015). PEDF, which promotes survival of retinal ganglion cells through STAT3 activation by PEDFR dependent signaling could be useful in neurodegenerative disorders (Eichler et al, 2017; Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent publication suggested that PEDF-mediated neuroprotection against oxidant injury is largely mediated via ERK1/2 and Bcl-2, indicating that PEDF preserves the viability of oxidative challenged neurons (Sanchez et al, 2011), and may be related to the inhibition of NADPH oxidase-mediated oxidative stress (Maeda, Matsui, Takeuchi, & Yamagishi, 2011 (Sagheer, Gong, & Chung, 2015). PEDF, which promotes survival of retinal ganglion cells through STAT3 activation by PEDFR dependent signaling could be useful in neurodegenerative disorders (Eichler et al, 2017;Huang et al, 2018).…”
Section: Pedf Detection In Serummentioning
confidence: 99%
“…Regarding neurodegenerative disorders, several studies suggested links between PEDF, EGF, TGF-β and PD/AD [ 113 , 114 , 115 , 116 ]. For example, EGF is lower in plasma of PD patients compared to healthy controls [ 113 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…In contrast, elevated level of TGF-β was found in CSF in AD [ 115 ]. Further, in AD the serum level of PEDF was decreased compared to two groups of healthy controls: middle-aged adults and older adults [ 116 ]. Altogether, the role of GFs as biomarkers requires further investigation.…”
Section: C-reactive Proteinmentioning
confidence: 99%